Annual bulletin of statistics on cocoa, coffee and tea : 1979/80 season - Nigerian Cocoa Board (Ibadan, Nigeria : Nigeria Cocoa Board, 1982)
This third edition of the Annual Bulletin of Statistics on cocoa, coffee, and tea. In it, there is the weekly production figures in respect of each of the producing states, beginning from 1979/80 cocoa season.
ne 08/04/2019
Ref
Keywords: Cocoa--Beverage.; Nigeria